Use of Used Materials as Learning Media in Increasing Student Science Process Skills - Maimunah H. Daud; Yuliana Yenita Mete (Postgraduate, University of Mataram, 2023)
Â This study aims to find out the use of used materials as learning media in improving the science process skills of class VII students of SMP SATAP Negeri 7 Ende. This type of research is a quantitative research, experimental method and uses a pre-experimental design and a one-shot case study model, that is, there is a group given a treatment/treatment and then the results are observed. The population in this study was all students of class VII SMP SATAP Negeri 7 Ende academic year consisting of two classes with a total of 44 students and the sample was class VIIA with 22 students. The sampling technique used is simple random sampling. The data obtained from the research sample is in the form of observation data on students' science process skills. Data analysis was performed by t-test. The results of the study show that the use of used materials as learning media can improve the science process skills of class VII students of SMP SATAP Negeri 7 Ende. This is evidenced by the value of tcount â‰¥ ttable, that is 8.466 â‰¥ 1.797 with a significant level of 0.05 and dk = 31 so that H0 is rejected and H1 is accepted (the proposed hypothesis is accepted).